Acinetobacter species and their antibiotic resistance profiles isolated from various clinical specimens between 2014 and 2018 (Annals of Medical Research, 2021)
Aim: Acinetobacter species have emerged as an important cause of nosocomial pneumonia and bloodstream infections, especially in immunocompromised patients with underlying pathologies. Worldwide, there has been a marked increase in resistance to most antimicrobial agents in recent years. The aim of this study was to evaluate Acinetobacter spp., their antimicrobial resistance rates and changes in resistance rates isolated from a tertiary hospital in a five-year period.Material and Methods: In this study, Acinetobacter strains isolated from inpatients or outpatients between January 2014 and December 2018 were included in the Medical Microbiology Laboratory of our hospital. BD Phoenix 100 (Becton Dickinson, USA) was used for identification and antibiotic susceptibility of the isolates.Results: Acinetobacter baumannii and A. baumannii - A. calcoaceticus complex constituted 91% of all isolates. Acinetobacter strains were mostly isolated from inpatients with pneumonia (37%) and soft tissue infections (22.5%). Colistin resistance was not observed between 2014 and 2016, but it was detected in 2017 and 2018. Colistin resistance was 2.5% and 12.6% in A. baumannii and 2.9% and 13.5% in A.baumannii-calcoaceticus complex in 2017 and 2018, respectively, and this increase was statistically significant. Colistin and tigecycline were the most effective agents in all isolates. The resistance rates of tigecycline in A.baumannii and A.baumanniicalcoaceticus complex strains were 11% and 14.3%, respectively. Extensively drug-resistant isolates were 91.7% and pan drugresistant isolates were 2.3%.Conclusion: It has been observed that resistance to all used drugs including colistin in Acinetobacter species increased and the rate of pan drug-resistant isolates were also elevated. Especially the significant increase in colistin resistance observed in recent years raises concern. In order to prevent and cope with the development of multiple resistance, each laboratory should determine the distribution of resistance in Acinetobacter species and in particular resistance to colistin.
Keywords: Acinetobacter species; antibiotic resistance; epidemiology; PDR; XDR